Penerapan Media Microsoft Word Pada Era Digital Dalam Dasar-Dasar Pengolahan Teks di MTS Muhammadiyah - Asrafil, Asrafil; Rahmawan, Ardi; Ramdhani, Lisda (Infomatika: Pendidikan Informatika, 2025)
The development of digital technology has brought significant changes in the field of education, particularly in the use of software such as Microsoft Word as a learning tool. This study aims to analyze students' understanding of basic and advanced features of Microsoft Word, identify obstacles faced in its academic use, and provide recommendations for effective mentoring strategies. A descriptive quantitative method was employed, using a Likert-scale questionnaire and semi-structured interviews involving 20 students from grades VII–IX and 2 teachers at MTS Muhammadiyah, Bima Regency. The results indicate a notable improvement in learning outcomes among students who actively used Microsoft Word compared to the control group, with the majority (70%) giving highly positive responses to its implementation. In addition to enhancing material comprehension and text processing skills, Microsoft Word has also proven effective in creating a more engaging and interactive learning environment. However, limitations in the use of advanced features were still observed due to insufficient guidance. Therefore, structured training for both teachers and students is essential to optimize the use of Microsoft Word in 21st-century digital learning